2014
DOI: 10.1016/j.nicl.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of neural motor networks is disrupted in children with developmental coordination disorder and attention-deficit/hyperactivity disorder

Abstract: Developmental coordination disorder (DCD) and attention deficit/hyperactivity disorder (ADHD) are prevalent childhood disorders that frequently co-occur. Evidence from neuroimaging research suggests that children with these disorders exhibit disruptions in motor circuitry, which could account for the high rate of co-occurrence. The primary objective of this study was to investigate the functional connections of the motor network in children with DCD and/or ADHD compared to typically developing controls, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
124
2
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(149 citation statements)
references
References 65 publications
14
124
2
9
Order By: Relevance
“…Functional deficits of the ventral attentional network (including the supramarginal and angular gyri) are well known in ADHD (Helenius et al, 2011;Cortese et al, 2012;McCarthy et al, 2013;McLeod et al, 2014) and right-ward hyperactivation of the angular gyrus (Cortese et al, 2012) and a left-ward hypoactivation of the ventral attention system (McCarthy et al, 2013) were previously observed in ADHD adults and could be in line with our connectivity results.…”
Section: Discussionsupporting
confidence: 92%
“…Functional deficits of the ventral attentional network (including the supramarginal and angular gyri) are well known in ADHD (Helenius et al, 2011;Cortese et al, 2012;McCarthy et al, 2013;McLeod et al, 2014) and right-ward hyperactivation of the angular gyrus (Cortese et al, 2012) and a left-ward hypoactivation of the ventral attention system (McCarthy et al, 2013) were previously observed in ADHD adults and could be in line with our connectivity results.…”
Section: Discussionsupporting
confidence: 92%
“…Recent findings have suggested an existence of common neurophysiological substrates underlying both motor and attention problems. 20 The present study also revealed statistically significant differences between the groups for most motor quotients assessed: fine and global motricity, balance, body schema, and spatial and temporal organization. Motor quotients for each domain demonstrated that typically developing children performed within the normal medium range, except for spatial organization.…”
Section: Discussionsupporting
confidence: 67%
“…The results suggest a combination of biological and shared environmental pathways linking coordination difficulty, anxiety and depression. One tentative suggestion for a potential biological mechanism which has been implicated in DCD (McLeod et al, 2014;Zwicker et al, 2010), and in both anxiety (Terasawa et al, 2012) and depression (Sprengelmeyer et al, 2011), is the atypical volume and functioning of the insular cortex (IC). The IC is central to processing information about the physiological state of the body, monitoring sensations and connecting to other systems, such as the anterior cingulate cortex, to allocate attention towards particular stimuli and to plan appropriate actions (Paulus and Stein, 2006).…”
Section: Discussionmentioning
confidence: 99%